ANALISIS PENDAPATAN USAHATANI JAGUNG MENGGUNAKAN ALAT TANAM (AGR-PN22 ) DI DESA OMBU-OMBU JAYA KECAMATAN KONAWE SELATAN - Syamsinar; Nurcayah; Sufa, Basri (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
Corn is one of Southeast Sulawesi's leading commodities with an area of ​​23,945 Ha with a productivity level of 28.64 tons/ha and is distributed in South Konawe Regency, Laeya District in Ombu-Ombu Jaya Village as the research area. The demand for corn for animal feed needs continues to increase while production capacity is still limited and the productivity and yields obtained by farmers are low, thus affecting the income of farmers, including those using Agrowindo type AGR-PN22 corn and grain planting equipment with a planting equipment capacity of 3, 7 kg and planting distance 22 cm, depth 3.5-7.8 cm with number of seeds 1-2 (can be adjusted). Analysis of costs and revenues is a variable in calculating farmer income. This research aims to determine the income of corn farming using planting tools (AGR-PN22) in Ombu-Ombu Jaya Village, Laeya District, South Konawe Regency. The results of the research show that the income from corn farming using the AGR-PN22 planting tool in Ombu-Ombu Jaya Village, Laeya District, South Konawe Regency is IDR 467,299,250 per planting season with an average farmer income of IDR 8,986,524 per planting season and income farmers per/ha amounting to IDR 10,867,424. The significance of the use of modern and traditional planting tools for corn plants has a significant impact on production and income, as the results of research conducted by Anugerah Fitri Amalia et al in Central Sulawesi regarding the comparison of the performance of corn and tubing planting tools on dry land in Sigi district, Central Sulawesi show that the performance of seed planters is better. higher than the tugal. Seed planters have an average theoretical field capacity of 1.92 ha/hour with a forward speed of 6.42 km/hour and an actual field capacity of 0.625 ha/hour, while in single plants the average theoretical capacity is 0.50 ha/hour with actual field capacity is 0.167 ha/hour.